Information Technology and Returns to Scale - Lashkari, Danial; Bauer, Arthur; Boussard, Jocelyn (American Economic Review, 2024)
What are the implications of the dramatic fall in IT prices for aggregate technology? When firm-level technologies are continuously differentiable, a factor price shock leads to (i) a substitution between factors and/or (ii) an endogenous response of returns to scale. The second channel is governed by the output elasticity of relative factor demand. Using detailed firm-level data from France, we estimate this elasticity to be positive for IT factor demand. A quantitative exercise accounting for both technological channels shows that falling IT prices can explain much of the changes in concentration and the composition of aggregate labor share in France. (JEL D22, D24, D33, E25, L63, L86)